USABILITY TESTING APLIKASI HI JOBS! MENGGUNAKAN TEKNIK PERFORMANCE MEASUREMENT DAN CONCURRENT THINK ALOUD - Kusuma, Olivia; Munir, Abdul; Surasa, Hendra (STMIK KHARISMA Makassar, 2023)
Hi Jobs! is a mobile application that will help people find work because it provides various information concerning job vacancies. This application is still relatively new and has never been tested before. However, this application already has several criticisms and suggestions from users regarding problems that had occurred when using the Hi Jobs! application. The problems that occurred were related to aspects of application usability. Therefore, usability testing is needed to determine the effectiveness, efficiency and user satisfaction when using the Hi Jobs! application using Performance Measurement and Concurrent Think Aloud techniques. The test was conducted on 20 participants who were divided into two categories, advanced and novice. The results of the study showed that advanced participants had a success rate of 96% with a total of one failed task, while novice participants had a success rate of 89% with a total of four failed tasks. The average time for participants in the advanced category was 30 seconds and the novice category was 37 seconds. Based on the results of interviews conducted, there were problems with 4 application features of the Hi Jobs! application. In conclusion, this application was very effective but it was not efficient nor has it meet user satisfaction because there are some features that are difficult to find. Therefore, recommendations for improvement have been made based on the received criticisms and suggestions to meet user satisfaction.